2012
DOI: 10.1116/1.4767233
|View full text |Cite
|
Sign up to set email alerts
|

Improved single ion implantation with scanning probe alignment

Abstract: Activation improvement of ion implanted boron in silicon through fluorine co-implantation J.Single dopant atoms can affect transport properties in scaled semiconductor devices and coherent control of spin and charge degrees of freedom of single dopant atoms promises to enable quantum computing. The authors report on an improved technique for deterministic placement of single dopant atoms by single ion implantation with scanning probe alignment. Ions are generated in a microwave driven ion source, mass analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 19 publications
0
11
0
Order By: Relevance
“…For instance, Toyli et al demonstrated lateral control of NVs by ion implanting through nanofabricated apertures 13 , but the resulting coherence times were relatively short (<~ 20 µs). Focused nitrogen-ion [14][15][16] and helium-ion 17 implantation can also localize NV centers but the resulting coherence times are either short, < 1 us, or not reported. Long NV coherence times (~ 700 µs) were demonstrated in nitrogen δ-doped diamond via carbon implantation through apertures 18 .…”
mentioning
confidence: 99%
“…For instance, Toyli et al demonstrated lateral control of NVs by ion implanting through nanofabricated apertures 13 , but the resulting coherence times were relatively short (<~ 20 µs). Focused nitrogen-ion [14][15][16] and helium-ion 17 implantation can also localize NV centers but the resulting coherence times are either short, < 1 us, or not reported. Long NV coherence times (~ 700 µs) were demonstrated in nitrogen δ-doped diamond via carbon implantation through apertures 18 .…”
mentioning
confidence: 99%
“…Therefore, the interaction of HCI with surfaces may not be described in terms of an equilibrium charge state dependent stopping force. Furthermore, due to the localization of the energy deposition slow HCI can be used as an efficient tool for surface nano-structuring [13][14][15][16][17][18][19][20][21][22][23][24] and tuning of the electrical properties of materials [25], as well as a probe for surface energy deposition processes [26,27]. Recently, it has been shown that slow HCI can create pores in 1 nm thick carbon nanomembranes (CNM) [28,29] mainly by deposition of their potential energy [30].…”
mentioning
confidence: 99%
“…Local NVformation without global thermal annealing also enables a try-andrepeat approach to NVarray formation. After a single nitrogen ion is implanted and registered in a selected location [5,9], an NVcenter can be formed by low energy electron irradiation, by targeted SHI irradiation [26], or by another form of local excitation [27,28]. The location can be repeatedly probed for the presence of an NVcenter by PL or CL.…”
Section: Outlook and Conclusionmentioning
confidence: 99%
“…In pure diamonds, nitrogen can be added by implantation of nitrogen ions [5][6][7][8]. Ion implantation offers control over the local nitrogen and NV center concentrations with high spatial resolution [5,9]. When implanting a diamond with nitrogen ions, e. g. of keV to MeV energies, ions transfer kinetic energy to carbon atoms in elastic collisions, leading to collision cascades that generate vacancies and carbon interstitials.…”
Section: Introductionmentioning
confidence: 99%